Anthrax of the gastrointestinal tract and oropharynx: CT findings - Ozdemir, Huseyin; Demirdag, Kutbettin; Ozturk, Tulin; Kocakoc, Ercan (Springer Heidelberg, 2010)
Anthrax is an acute infection caused by the Gram-positive organism Bacillus anthracis. It causes cutaneous, respiratory, and gastrointestinal (GI) infections in humans. We present the computed tomography findings of anthrax of the GI tract and oropharyngeal involvement which include inflammatory lesion in the oropharynx and GI hemorrhage.
Keywords: Anthrax; Oropharynx; Computed tomography